2012
DOI: 10.1037/a0024463
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution of attention within and across objects.

Abstract: Attention operates to select both spatial locations and perceptual objects. However, the specific mechanism by which attention is oriented to objects is not well understood. We examined the means by which object structure constrains the distribution of spatial attention (i.e., a “grouped array”). Using a modified version of the Egly et al. object cuing task, we systematically manipulated within-object distance and object boundaries. Four major findings are reported: 1) spatial attention forms a gradient across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
52
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 77 publications
(165 reference statements)
7
52
1
Order By: Relevance
“…However, caution should be taken in interpreting these results, for there is evidence that spatial attention does not necessarily shift in an analog fashion (e.g., C. W. Eriksen & Murphy, 1987;Yantis, 1988). Perhaps the role of space in object-based selection is best illustrated in a recent study by Hollingworth, Maxcey-Richard, and Vecera (2012), who found interaction between space-and object-based attention within the same experimental paradigm. Consistent with the notion that there are linkages between lowerlevel spatial representations and higher-level spatially invariant representations at multiple levels of selection (Di Lollo, Enns, & Rensink, 2000;Hochstein & Ahissar, 2002;Roelfsema & Houtkamp, 2011;van der Velde & de Kamps, 2001), Hollingworth et al showed that whereas spatial attention forms a gradient across an attended object, the spread of this gradient is constrained by the boundaries of the object.…”
Section: Mechanisms That Give Rise To Object Effectsmentioning
confidence: 93%
“…However, caution should be taken in interpreting these results, for there is evidence that spatial attention does not necessarily shift in an analog fashion (e.g., C. W. Eriksen & Murphy, 1987;Yantis, 1988). Perhaps the role of space in object-based selection is best illustrated in a recent study by Hollingworth, Maxcey-Richard, and Vecera (2012), who found interaction between space-and object-based attention within the same experimental paradigm. Consistent with the notion that there are linkages between lowerlevel spatial representations and higher-level spatially invariant representations at multiple levels of selection (Di Lollo, Enns, & Rensink, 2000;Hochstein & Ahissar, 2002;Roelfsema & Houtkamp, 2011;van der Velde & de Kamps, 2001), Hollingworth et al showed that whereas spatial attention forms a gradient across an attended object, the spread of this gradient is constrained by the boundaries of the object.…”
Section: Mechanisms That Give Rise To Object Effectsmentioning
confidence: 93%
“…Spatial cueing effects within objects Later spatial cueing studies started to introduce object contours that surrounded both the cue and target and to examine the effect of such object contour presence on the distribution of spatial attention (e.g., Egly et al, 1994;Hollingworth, Maxcey-Richard, & Vecera, 2011;Reppa, Fougnie, & Schmidt, 2010;Robertson & Kim, 1999). These studies have shown that within-object locations can be coded in object-centred frames of reference (Fig.…”
Section: Space-based Effects Of Spatial Cueingmentioning
confidence: 99%
“…For instance, cueing effects can increase with increasing cue-target distance, both in the space between different objects (e.g., Downing & Pinker, 1985) and in the space within objects (e.g., Egly et al, 1994;Hollingworth et al, 2011). Furthermore, just as with space between objects, locations in the space along an object's A. Location-based selection in a viewer-centred reference frame C. Location-based selection in an object-centred reference frame B. Object-based selection in a scene-based reference frame E. Location-and part-based selection in viewer-and object-centred reference frames D. Location-and object-based selection in viewer-centred and scene-based reference frames with the environmental location relative to the viewer (viewer-centred frames of reference yielding location-based spatial cueing effects).…”
Section: Space-based Effects Of Spatial Cueingmentioning
confidence: 99%
“…In vision, several studies have demonstrated that these pathways interact with one another in spatial selective attention (e.g. Baylis & Driver, 1992;Egly, Driver, & Rafal, 1994;Hollingworth, Maxcey-Richard, & Vecera, 2012;Marino & Scholl, 2005;Martinez, Ramanathan, Foxe, Javitt, & Hillyard, 2007). For example, Egly et al (1994) presented long outline rectangles either above and below fixation (horizontal objects), or left and right of fixation (vertical objects).…”
Section: Introductionmentioning
confidence: 99%